2023
DOI: 10.1002/ctm2.1440
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotyping of the lipidomic response in COVID‐19 and non‐COVID‐19 sepsis

Hu Meng,
Arjun Sengupta,
Emanuela Ricciotti
et al.

Abstract: BackgroundLipids may influence cellular penetrance by viral pathogens and the immune response that they evoke. We deeply phenotyped the lipidomic response to SARs‐CoV‐2 and compared that with infection with other pathogens in patients admitted with acute respiratory distress syndrome to an intensive care unit (ICU).MethodsMass spectrometry was used to characterise lipids and relate them to proteins, peripheral cell immunotypes and disease severity.ResultsCirculating phospholipases (sPLA2, cPLA2 (PLA2G4A) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…The lipidomics data revealed how the lipidome controls the immune response and its effect on sepsis severity depending on the COVID-19 status. Expression of inflammatory hubs responsible for restricting inflammation, such as ChoE-18 : 3, LPC-O-16 : 0, and PC-O-30 : 0, is decreased in patients with sepsis from COVID-19, while expression of inflammatory hubs responsible for enhancing inflammation, such as sPLA2, PGD2, and 12-HETE, is increased in patients with sepsis from COVID-19 as reported by Meng et al 141 Data from a multi-omics approach using proteomics, metabolomics, and lipidomics were applied to build a workflow to predict aggravation of COVID-19 symptoms of patients in the ICU. Two proteins (CCL7 and CA14), as well as one lipid (HexCer 18 : 2; O2/20 : 0), were identified as short-term predictors of worsening COVID-19 progression in ICU patients as described by Kugler et al 142 …”
Section: Examples Of Omics and Multiomics Studies Focused On Health A...supporting
confidence: 53%
“…The lipidomics data revealed how the lipidome controls the immune response and its effect on sepsis severity depending on the COVID-19 status. Expression of inflammatory hubs responsible for restricting inflammation, such as ChoE-18 : 3, LPC-O-16 : 0, and PC-O-30 : 0, is decreased in patients with sepsis from COVID-19, while expression of inflammatory hubs responsible for enhancing inflammation, such as sPLA2, PGD2, and 12-HETE, is increased in patients with sepsis from COVID-19 as reported by Meng et al 141 Data from a multi-omics approach using proteomics, metabolomics, and lipidomics were applied to build a workflow to predict aggravation of COVID-19 symptoms of patients in the ICU. Two proteins (CCL7 and CA14), as well as one lipid (HexCer 18 : 2; O2/20 : 0), were identified as short-term predictors of worsening COVID-19 progression in ICU patients as described by Kugler et al 142 …”
Section: Examples Of Omics and Multiomics Studies Focused On Health A...supporting
confidence: 53%
“…Analysis of patients with sepsis revealed that although PGD 2 is elevated in patients with sepsis of bacterial or viral origin, it has a relative selectivity for sepsis induced by SARS-CoV-2. 226 Indeed, genetic deletion or pharmacological inhibition of DPr1 protects aged mice from lethal SARS-CoV-2 infection. 227…”
Section: Pgd2 In the Cardiovascular Systemmentioning
confidence: 99%
“…Prostanoids in serum from mice and cell culture media of mouse aortas were measured, as described by Meng et al 15 Blood Loss by Tail Amputation in Hyperlipidemic Mice (Ldlr −/− ) Mice were used in this experiment after feeding a high-fat diet (HFD) for 12 weeks; 2 mm of the tail was amputated using a sterile scalpel under anesthesia with ketamine/xylazine/ acepromazine. Blood was collected into a preweighed glass tube containing Drabkin reagent to estimate the amount of blood loss and hemoglobin content at 420 nm using a microplate reader.…”
Section: Mass Spectrometric Analysis Of Serum and Cell Culture Media ...mentioning
confidence: 99%